Service learning at Universidade Católica Viseu – a pilot study - Veiga, N. (2021)
Some of the concepts of Service Learning (SL) are common to the teaching of health-related areas. However, there are many other requisites for a project to be SL such as the developing of student’s commitment to contribute to society and the importance of reflection on the learning experience. In this presentation the application of the SL methodology to Health in the Centro Regional de Viseu of the Universidade Católica Portuguesa, where students from the Integrated Master of Dental Medicine as well as the Bachelors in Management get together to help a senior nursing home to improve the oral health of the residents and the financial management of the home. The project is only half completed so far and there are still goals to accomplish. However, students’ portfolios already show that the 51 students involved in treating about 200 elderly residents are happy to participate in the project. These students are working closely with the Home managers and employees to improve oral health and prevent oral diseases. This pilot intervention is part of a larger project which aims at implementing SL in the Universidade Católica Portuguesa as well as to identify good practices in SL in Portugal.